Post-syncope trauma should be considered in COVID-19 patients - Ghanbarpour, Fatemeh; Ghahestani, Seyed Mohammad; Sharifian, Rayka (Archives of Men's Health, 2020)
In December 2019, a new form of respiratory infection associated with coronavirus appeared in Wuhan, China. As of today, COVID-19 has spread all around the world. There have been 9.24 million confirmed cases and 477,000 deaths globally. Fever, cough, and coexistence chest or back pain are some of the most reported symptoms of COVID-19. Although syncope is not a primary symptoms, we see patients passing out in the street after coronavirus pandemic. Up to now, syncope due to COVID-19 has only been reported by CHANTAL and coauthor in a 79 year-old patient. (1) There is no available data on syncope in COVID-19 patients. This is while some patients have been referred to us purely for their symptoms of fainting. Etiology of fainting in COVID-19 may be the product of orthostatic hypotension and vasovagal syncope due to dehydration. Increasing pressure in thoracic cavity during sequential cough may induce “cough syncope”